Supply Chain Pattern in Digital for Research Management for ASEAN University Network Quality Assurance - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The researchabout the supply chain pattern in digital for research management for asean university network quality assurance. The objectives of researchto design and to assess the suitability of supply chain pattern in digital for research management for asean university network quality assurance. The sample group consisted of fifteen experts in the field of information system ,supply chain and research. The data is analyzed by means and standardized deviations statistically. The research result shows that supply chain pattern in digital for research management for asean university network quality assuranceis consisted of 5 key elements which are 1) main elements 2) suppliers 3) university 4) customers 5)consumer. The results from experts supply chain pattern in digital for research management for asean university network quality assurance was a high level. It showed that supply chain pattern in digital for research management for asean university network quality assurance could be used to develop the tasks.